Clinical Study of 8 Cases of CHD2 Gene Mutation–Related Neurological Diseases and Their Mechanisms - Luo, Xiaona; Sun, Xiaoang; Wang, Yilin; Lin, Longlong; Yuan, Fang; Wang, Simei; Zhang, Wenjing; Ji, Xiaobing; Liu, Meiyan; Wu, Shengnan; Lan, Xiaoping; Zhang, Jie; et al. (Frontiers in Cell and Developmental Biology, 2022)
Background: The chromodomain helicase DNA-binding protein 2 (CHD2) gene, is an ATPase and part of the CHD family of chromatin remodelers. Mutations in the CHD2 gene are inherited in an autosomal-dominant manner and can lead to intellectual disability, epilepsy, and autism. We investigated the clinical characteristics of CHD2-related conditions and their possible pathogenesis. Methods: We collected and analysed the clinical data of patients that were identified as having CHD2 mutations. Genetic testing was performed using targeted sequencing or whole-exome sequencing. We analysed the expression of CHD2 and repressor element 1-silencing transcription factor (REST) in blood samples using quantitative PCR and the conservation of the mutations. The CHD2 mutations we identified were compared with the known mutations reported in the CHD2-related literature. Results: Eight patients with CHD2 gene mutations were analysed. 6 mutations were identified; four were unreported previously (c.670C>T; c.4012A>C; c.2416dup; c.1727–1728insAT), and two were known mutations: c.5035C>T (2 cases) and c.4173dup (2 cases). Among these mutations, seven were de novo mutations, and one could not be determined because the parents refused genetic testing. The clinical manifestations included mild or severe intellectual disability, epilepsy, and behavioural abnormalities. Quantitative PCR showed that the CHD2 gene expression levels among the patients, parents, and the controls were not significantly different. The levels of REST gene expression in the patients were significantly higher than those of the controls; thus, mutation of the CHD2 gene led to an increase in the expression level of the REST gene. The mutations reported were all located in conserved positions in different species. Among the various medications administered for treatment, valproate showed the best results for the treatment of epilepsy caused by CHD2 gene mutation. Conclusion: Mutation in CHD2 did not lead to a significant decrease in its expression level, indicating that the clinical phenotype was unrelated to its expression level, and the mutant protein may retain some function. Most of the mutations relatively stable. In addition, the clinical manifestations from the same mutation in the CHD2 gene were different among the known cases; this may be related to the regulation of REST or other regulatory factors.